Analysis of the Science of Hadith and its Scientific-Practical and Educational Significance - Oygul Hamdamova (Genius Publishing Group, 2023)
Researching the invaluable scientific and spiritual heritage of the great scholars and thinkers who lived and created in our country, translating and popularizing the works they left behind, as well as collecting electronic copies of manuscripts stored in libraries and archives in foreign countries and delivering them to our people are becoming urgent issues. The article talks about the emergence of hadiths, the science of hadith, the educational importance of hadiths in the development of Islamic civilization and human development, the scientific and practical importance of using hadiths in the training of hadith scholars, examples of hadiths and their content.
Keywords: hadith; hadith science; Islamic civilization